Acinetobacter baumannii Is an opportunistic pathogen as an MDRO especially on intensive ward - Suranadi, I Wayan; Dwi Fatmawati, Ni Nengah; Aryabiantara, I Wayan; Sinardja, Cynthia Dewi; Saputra, Darmawan Jaya (Bali Journal of Anesthesiology, 2019)
Acinetobacter baumannii is an opportunistic bacterial pathogen that is associated with hospital acquired infections and is a major cause of nosocomial infections especially in intensive spaces; this is becoming increasingly a widespread concern in various hospitals around the world. Acinetobacter baumannii, which is resistant to many antibiotics, is now recognized as clinically very important. Reports suggest that the spread of A. baumannii in the hospital environment led to an increase in nosocomial outbreaks associated with high mortality rates. However, many other Acinetobacter spp. can also cause nosocomial infections. This review focuses on the role of Acinetobacter spp. as nosocomial pathogens, resistance patterns and epidemiology.